2022
DOI: 10.1108/jbim-11-2021-0512
|View full text |Cite
|
Sign up to set email alerts
|

Actor engagement: origin, evolution and trends

Abstract: Purpose This paper aims to present the literature review on engagement in marketing, specifically on the concept of actor engagement (AE), to identify the most influential countries, authors, journals and institutions, their structure and research lines. Design/methodology/approach This review was carried out from a bibliometric and network analysis of documents published in the Scopus and Web of Science databases. Findings A total of 223 documents were found that were scientifically mapped in this field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 106 publications
0
3
0
1
Order By: Relevance
“…The tool allows evaluating bibliometric indicators such as the annual scientific production, authors, countries, and most relevant institutions. The choice responds to the fact that it is a software compatible with multiple databases, it has a variety of easy-to-use bibliometric functionalities, it allows the creation of research trends in a simple way and has been used in multiple research (Aria and Cuccurullo, 2017; Aristizábal et al ., 2021; Barrera Rodríguez et al. , 2023; Bond et al ., 2019; Demiroz and Haase, 2019; Duque and Cervantes-Cervantes, 2019; Duque-Hurtado et al ., 2020; Torres et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The tool allows evaluating bibliometric indicators such as the annual scientific production, authors, countries, and most relevant institutions. The choice responds to the fact that it is a software compatible with multiple databases, it has a variety of easy-to-use bibliometric functionalities, it allows the creation of research trends in a simple way and has been used in multiple research (Aria and Cuccurullo, 2017; Aristizábal et al ., 2021; Barrera Rodríguez et al. , 2023; Bond et al ., 2019; Demiroz and Haase, 2019; Duque and Cervantes-Cervantes, 2019; Duque-Hurtado et al ., 2020; Torres et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above, it is important to indicate that the methodological procedure used in this research is based on the structure suggested by Donthu et al (2021), whose implementation is developed in four (4) stages, which are described in Figure 1. It has also been used in previous studies (Barrera et al, 2022;Castellanos et al, 2022;Duque et al, 2020Duque et al, , 2021Hoyos et al, 2023;Loaiza et al, 2022;Restrepo et al, 2023;Robledo et al, 2023).…”
Section: Visualization and Analysismentioning
confidence: 99%
“…El proceso para llevar a cabo el análisis bibliométrico y la revisión narrativa de la literatura se basó en las recomendaciones, métodos y experiencia bibliográfica de varios autores (Arksey & O'Malley, 2005;Badger et al, 2000;Barrera Rodríguez et al, 2022;Boell & Cecez-Kecmanovic, 2010;Denney & Tewksbury, 2013;Ferrari, 2015;García Salazar et al, 2021;Manterola et al, 2013;Mejía-Franco et al, 2021;Pickering & Byrne, 2014;Sorrell, 2007;Tranfield et al, 2003;van Wee & Banister, 2016). Los mencionados investigadores plantean, de manera general, las etapas relacionadas con la estructuración del análisis bibliométrico y narrativo de la bibliografía disponible en términos de identificación de las preguntas a responder; definición del método de búsqueda, recopilación, definición de los criterios de inclusión y exclusión de los documentos, descripción y análisis de la información, y planteamiento de los principales resultados.…”
Section: Metodologíaunclassified